1966
DOI: 10.2136/sssaj1966.03615995003000060026x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties Affecting Dieldrin Toxicity to Drosophila melanogaster

Abstract: The toxicity to Drosophila melanogaster Meigen of dieldrintreated soils was measured by bioassay. Under adequate standardization and control of light, temperature, humidity, and soil moisture, the variation in insecticidal activity was closely related to the colloidal properties of the soils. As organic carbon content, specific surface area of the minerals, and soil reaction increase, higher levels of dieldrin were required to maintain the killing power. Cation‐exchange capacity interacts with soil organic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1969
1969
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…He postulated that decreases in toxicity were due to "bonding" to various soil fractions. Higher levels of dieldrin were required to maintain toxicity to D. melanogaster as organic carbon content, specific surface area, and soil reaction increased (Hermanson and Forbes 1966). The efficacy of chlorpyrifos was reduced in soils with high organic matter content, but pH had no effect on toxicity (Whitney 1967).…”
Section: Universify Microfilms Internationalmentioning
confidence: 99%
“…He postulated that decreases in toxicity were due to "bonding" to various soil fractions. Higher levels of dieldrin were required to maintain toxicity to D. melanogaster as organic carbon content, specific surface area, and soil reaction increased (Hermanson and Forbes 1966). The efficacy of chlorpyrifos was reduced in soils with high organic matter content, but pH had no effect on toxicity (Whitney 1967).…”
Section: Universify Microfilms Internationalmentioning
confidence: 99%
“…All the evidence indicates that the more organic matter is in a soil, the longer an insecticide persists in it, for instance, Edwards et al (1957) found a highly significant correlation between the persistence of aldrin and lindane, and the amount of organic matter in ten greatly differing soils. They postulated that the relationship between the persistence of insecticides and the amount of organic matter in soils was curvilinear, so that the persistence in muck soils could not be predicted by a simple linear equation, and this was confirmed by Hermanson and Forbes (1966).…”
Section: Organic Matter Contentmentioning
confidence: 99%
“…The adsorption of pesticides onto soil colloids was reviewed by Bailey and White (I964) and they calculated this was a phenomenon that greatly affected pesticide peristence. Hermanson and Forbes (1966) concluded that the persistence of dieldrin in soils was closely related to their colloidal properties and the specific surface area of the minerals they contained. Edwards et al (I957) compared the correlations between persistence of insecticides and moisture-holding capacity (r = 0.8468 for aldrin, r = 0.8204 for lindane) with those between persistence and organic matter content (r = 0.8935 for Pesticide Residues in Soil and Water 425 aldrin, r = 0.9141 for lindane), and concluded that, although moistureholding capacity which in turn correlated with clay content, was important, it was less so than the amount of organic matter.…”
Section: Clay Contentmentioning
confidence: 99%
See 2 more Smart Citations